Comparing methods of ileostomy closure constructed in colorectal surgery in Turkey - Dinc, Bulent; Ay, Nurettin; Ciyiltepe, Huseyin (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Stoma construction is a life saver method for emergent and elective operations in colorectal surgery. However, they are associated with high rates of morbidity and mortality. Aim: To compare the operative findings, early postoperative complications, and costs of stapled and hand-sewn closures in loop ileostomies that are constructed in emergent and elective colorectal surgery. Material and methods: The data of 68 patients requiring loop ileostomies during colorectal surgery were retrospectively evaluated. SPSS (version 20) was used for data analysis. Results: The study group consisted of 44 men and 24 women with a mean age of 55.5 years. The ileostomy closures were performed with hand-sewn method in 36 patients (group 1) and stapled method in 32 patients (group 2). The mean operation time was 75.4 min in group 1 and 46.7 min in group 2 (p < 0.001). Early postoperative complications were wound infection (8.8%), small bowel obstruction (6.06%), and anastomotic leakage (2.9%). Total costs, flatulence and faeces outlet time, oral feeding starting time, time of hospital stay, and early postoperative complications were lower in the stapled group. Conclusions : Morbidity and mortality rates of stoma construction and its closure are still considerable. Lower anastomotic leakage rate, complication rate, and costs and shorter operative times in the stapled group make this method preferable.